2015
DOI: 10.1002/adfm.201503115
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Polymeric Hybrid Micelles with Highly Tunable Properties to Co‐Deliver MicroRNA‐34a and Vismodegib for Melanoma Therapy

Abstract: wileyonlinelibrary.comA polymeric hybrid micelle (PHM) system with highly tunable properties is reported to co-deliver small molecule and nucleic acid drugs for cancer therapy; this system is structurally simple and easy-to-fabricate. The PHM consists of two amphiphilic diblock copolymers, polycaprolactone-polyethylenimine (PCL-PEI) and polycaprolactone-polyethyleneglycol (PCL-PEG). PHMs are rationally designed with different physicochemical properties by simply adjusting the ratio of the two diblock copolymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 44 publications
1
27
0
Order By: Relevance
“…Colocalization of mixed micelles with endosome/lysosome (visible as yellow fluorescence) was observed 5 min and 2 h after micelles were added to cells. The overlaps with the lysotracker staining revealed that the mixed micelles were efficiently taken up into the endosome/lysosomal compartments, indicating a lysosomal pathway after internalization . And both PPN MM and PPF MM showed extensive distribution in the cytoplasm.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Colocalization of mixed micelles with endosome/lysosome (visible as yellow fluorescence) was observed 5 min and 2 h after micelles were added to cells. The overlaps with the lysotracker staining revealed that the mixed micelles were efficiently taken up into the endosome/lysosomal compartments, indicating a lysosomal pathway after internalization . And both PPN MM and PPF MM showed extensive distribution in the cytoplasm.…”
Section: Resultsmentioning
confidence: 90%
“…Polycaprolactone (PCL) is a biodegradable polymer that has been approved by the US Food and Drug Administration for applications in the human body such as sutures, tissue scaffolds, and adhesion barriers . PCL‐derived diblock copolymers have been extensively used in controlled release and targeted drug delivery . Herein, we report the synthesis of a d ‐fructose conjugated diblock copolymer poly(ε‐caprolactone)‐poly(ethylene glycol) (PCL‐PEG‐Fru) via click chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Among the available delivery systems, biodegradable polymeric nanoparticles have been the most successful delivery platforms used in drug/nucleic acid combinations [810]. Polymeric nanoparticles are typically composed of pharmacologically inert polymer suitable for encapsulation of both types of therapeutic cargos [11]. However, the manufacturing complexity and unsatisfactory drug loading ability of the traditional nanoparticles remain a significant hurdle for their clinical translation.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer hybrid micelles (PHMs), consisting of different amphiphilic diblock copolymers, have become promising carriers for co-delivery of nucleic acids and small-molecule drugs 10 . In general, nanoparticle-based drug delivery systems can efficiently co-deliver hydrophobic drugs and nucleic acids to tumors 11 - 13 .…”
Section: Introductionmentioning
confidence: 99%